2010
DOI: 10.7326/0003-4819-152-6-201003160-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Salsalate on Glycemic Control in Patients With Type 2 Diabetes

Abstract: Background Salsalate, a nonacetylated prodrug of salicylate, has been shown to decrease blood glucose concentration in small studies. Objective To compare the efficacy and safety of salsalate at different doses in patients with type 2 diabetes. Design Parallel randomized trial with computer-generated randomization and centralized allocation. Patients and investigators, including those assessing outcomes and performing analyses, were masked to group assignment. (ClinicalTrials.gov registration number: NCT00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
231
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(256 citation statements)
references
References 34 publications
14
231
0
6
Order By: Relevance
“…TNF-α inhibitors and salsalate, a prodrug of salicylic acid with inhibitory effects on the NF-κB pathway, have also been tested in T2D [60][61][62][63]. The positive results seen in these studies are consistent with the concept of targeting inflammation to treat T2D.…”
Section: Inflammation As the Therapeutic Target Against T2dsupporting
confidence: 64%
“…TNF-α inhibitors and salsalate, a prodrug of salicylic acid with inhibitory effects on the NF-κB pathway, have also been tested in T2D [60][61][62][63]. The positive results seen in these studies are consistent with the concept of targeting inflammation to treat T2D.…”
Section: Inflammation As the Therapeutic Target Against T2dsupporting
confidence: 64%
“…Salsalate, prodrug of salicylate, which unlike aspirin and sodium salicylate does not lead to bleeding risk, can improve insulin sensitivity and glucose control in prediabetic and T2DM patients with a good safety profile [74,75]. More particularly, a large randomized trial, the Targeting Inflammation with Salsalate in Type 2 Diabetes (TINSAL-T2D) trial, concluded that salsalate improves glucose control in T2DM patients with decrease in fasting glucose and glycated haemoglobin levels and enhances lipid profile [75]. These data suggest that NF-κB pathways may represent a novel therapeutic target for prevention and treatment of T2DM.…”
Section: Salicylate and Salsalatementioning
confidence: 99%
“…Data from epidemiological studies have demonstrated that increased levels of proinflammatory immune mediators and decreased levels of the anti-inflammatory adipokine adiponectin precede the onset of diabetes by many years [1][2][3]. Several approaches to attenuate subclinical inflammation in type 2 diabetes have improved glycaemic control [4][5][6][7][8], underscoring the clinical relevance of the inflammatory processes in the regulation of glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%